Missing ingredients for a lifestyle recipe to treat hypertension - Blumenthal, James A.; Sherwood, Andrew (Journal of Thoracic Disease, 2018)
Two decades ago, the DASH-Sodium study examined the impact of the Dietary Approaches to Stop Hypertension (DASH) diet and three different levels of sodium consumption on clinic blood pressure (BP) in a sample of 421 overweight or obese adults >21 years old with high normal BP and hypertension (1). Participants were randomized either to a control diet, typical of what is consumed by many Americans, or to the DASH diet, which is high in low fat dairy products and emphasizes fruits and vegetables, whole grains and nuts, fish and poultry, and smaller amounts of red meat and sweets compared to the typical American diet.